Pengaruh Keputusan Investasi, Kebijakan Deviden, serta Keputusan Pendanaan terhadap Nilai Perusahaan Manufaktur di Bursa Efek Indonesia - Luh Putu Novita Sartini; Ida Bagus Anom Purbawangsa (Faculty of Economics and Business Udayana University, 2014)
Thi s study aimed to examine effect of investment decisions, dividend policy and financing deci sions on f irmvalue of manufacturing companies. Thi s research was conducted at Indonesia Stock Exchange (BEI) withr esear ch period of 2009-2011. The amount of sample was 20 companies. The sampling method used waspurposive sampling method. Analysis technique used in this research was path analysis. The results showthat Investment decisions has signif icant posit ive effects on dividend policy, investment decisions wassignificant posit ive effect s on firm value, dividend pol icy signif icant positive effect to firm value, f inancingdecisions significant posi tive affects to firm value, and dividend policy has signi ficant positive ef fect onfinancing decisions